Análise comparativa de modelos digitais de terreno (MDT) como apoio no dimensionamento de projetos de saneamento - MESQUITA, Daniel Alvino (Universidade Federal do Pará, 2019)
In Brazil, when it is a question of information about the terrain relief characteristic, mainly in the North and Northeast regions, there is a lack of planialtimetric data, something that indirectly hinders the management and the planning of the cities, in relation to the design and elaboration of sanitation projects. In this way, it is possible to study methods and techniques that reduce the cost-benefit, highlighting the application of Digital Terrain Models (TDM) for better representation of the terrestrial surface. This work has as main objective the comparison of MDTs elaborated from different techniques, as well as to evaluate the implications of these in the water supply project and in the delimitation of water basin and drainage. The municipal seat of Ipixuna do Pará-Pá was adopted as a study area and two techniques were used to obtain altimetric data, namely: through SRTM images (Shuttle Radar Topographic Mission) and by topographic survey with Total Station. The interpolation kriging method was applied to generate the contour lines, aiming to subsidize the generation of MDT. Despite the good correlation obtained between the two MDTs generated. The Pearson correlation indexes of 0.85, agreement index of 0.97 and the performance index of 0.82 indicated that there is a good correlation between the altimetric data allowing the use of SRTM imaging in engineering projects. However, 72.5% of the points presented SRTM image scores higher than the Total Station altimetric data, with a difference between the 2.06 meter sources, indicating that due to the spatial resolution of the SRTM there is a disagreement in the delimitation of the basins for areas smaller than 1.73 km².